Patryk Kurdyla. The Forgotten Activists: Czechoslovakia’s Slovakian Dissident - Kurdyla, Patryk (Young Scholars Grinchenko – Seton International Journal, 2022)
The Slovak dissident movement’s role in the downfall of communism in Czechoslovakia has often been underemphasized in favor of a greater focus on its more well-known Czech counterpart. However, an examination of this resistance movement’s motivations gives a critical insight into the immense cultural differences between the Czechs and Slovaks, which would contribute to Czechoslovakia’s eventual dissolution. Ethnic as well as religious grievances motivated Slovak dissidents’ acts of defiance against the Communist regime, which repressed religious institutions such as the Catholic Church. These factors would slowly erode Communist officials’ hold on power, as they saw their authority publicly challenged by large segments of the population.